Vasculitic Tibial Mononeuropathy Associated with Inherited Immune Dysregulation: A Review of Tibial Mononeuropathies with Electrodiagnostic Considerations - James Liu; Yue Ding; Sandra Camelo-Piragua; James Richardson (Case Reports in Neurological Medicine)
Compressive tibial mononeuropathies are uncommon and can be caused by conditions including posterior compartment syndrome, soleal sling syndrome, and tarsal tunnel syndrome. Therefore, it is critical to consider noncompressive etiologies when a tibial mononeuropathy is suspected. This is a patient with a history of rare inherited immune dysregulation that presented to the electrodiagnostic laboratory with severe neuropathic pain in the right foot associated with plantarflexion weakness, concerning for a tibial mononeuropathy. However, the patient’s clinical presentation and results on electrodiagnostic testing were not consistent with any of the above entities. Therefore, noncompressive etiologies of tibial mononeuropathies such as vasculitis had to be considered. The patient subsequently underwent sural nerve biopsy which confirmed small-vessel vasculitis as the cause of the tibial mononeuropathy. She was then started on appropriate immunosuppressive treatment which resulted in significant pain relief and was discharged home. This case highlights the importance of considering noncompressive causes of tibial nerve injury. Compressive and vasculitic tibial mononeuropathies along with their electrodiagnostic considerations are reviewed. Furthermore, this case highlights the critical role of the electromyographer and ability to maximize the impact on patient care through a solid foundation in anatomy, pathophysiology, and electrodiagnosis blended with clinical acumen.